2004
DOI: 10.1002/app.20637
|View full text |Cite
|
Sign up to set email alerts
|

Cationized milled pine bark as an adsorbent for orthophosphate anions

Abstract: More efficient adsorption media are needed for removing dissolved phosphorus in surface water runoff. We studied the use of cationized pine bark as a sorbent for dissolved phosphorus in water. Cationized pine bark was prepared by treating extracted milled pine bark with polyallylamine hydrochloride (PAA HCl) and epichlorohydrin (ECH) in aqueous medium. Attachment of PAA HCl to the bark was monitored by percentage of weight gain and nitrogen content. Changes in bark surface chemistry were characterized by zeta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Different types of clays, such as hydroxyapatite, fluorspar, quartz activated with ferric ions, calcite, and quartz, are useful for the removal of fluoride (Chidambaram et al, 2003;Fan et al, 2003). Tshabalala et al (2004) reported cationized pine bark to be a good remover of orthophosphate from water.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of clays, such as hydroxyapatite, fluorspar, quartz activated with ferric ions, calcite, and quartz, are useful for the removal of fluoride (Chidambaram et al, 2003;Fan et al, 2003). Tshabalala et al (2004) reported cationized pine bark to be a good remover of orthophosphate from water.…”
Section: Introductionmentioning
confidence: 99%
“…Pine bark has a complex chemical structure consisting of both extractable and non-extractable components, of which the nonextractable can adsorb cationic polyelectrolytes [8]. Metals are thought to sorb to pine bark by ion exchange at a multitude of ionic sites, both cationic and anionic, with metal ions replacing adjacent hydroxyl groups to form a chelate [23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…Pine bark, a by-product from the forest industry, is particularly effective in removing metals from solution [3][4][5][6], storm water run off [7] and landfill leachate [1]. In addition to retaining metals, pine bark has also been shown to efficiently remove phosphorous [8], lindane [9], pentachlorphenol [10,11] and uranium [12] from water. However, one important problem with using pine bark as a filter is the release, or desorption, of contaminants from the unused filter material, particularly during the initial filtration phase.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the effect of pH and desorption results, Anirudhan et al (2006) and Namasivayan and Sangeetha (2004) concluded that ion exchange and chemisorption mechanisms could be important pathways for the removal of P by quaternized banana stem and ZnCl2 activated carbon, respectively. Tshabalala et al (2004) ions onto cationized milled wood residues. From P surface loading and spectroscopic analysis results, Shin et al (2005) claimed that ion exchange and surface precipitation could contribute to the elimination of P by La(III) treated juniper bark fiber.…”
Section: Co-existing Mechanismsmentioning
confidence: 99%